Safety evaluation of fermented fish and shellfish product II. Physical contaminants - Mabesa, R.C; Castillo, M.M; Bandian, V.T (1983)
Fermented fish and shellfish products collected from different regions of the Philippines from December, 1980 to December 1981 were analyzed microscopically for physical contaminants. The most common items found were seaweed parts and stones. Insect and leaf stems ranked next while wood scraps and hair were occasionally detected.